A modified rabbit model of tracheal stenosis and a household endoscope. More simplicity and accessibility - Zhang,Guoying (2020)
Abstract Purpose: To develop a simpler animal model for benign tracheal stenosis and introduce a low-cost household endoscope for postmodeling endotracheal evaluation. Methods: Twenty rabbits were randomly divided into a model group (15 rabbits, subjected to transoral nylon brush scraping of the trachea) and a mock group (5 rabbits, merely exempted from scraping), a household endoscope was then introduced for weekly endoscopic examination. Meanwhile, other 15 rabbits (modeling like the model group) underwent batch tracheal resection at different postintervention times for pathological analysis. Results: The model group presented a low mortality and few complications. The endoscope could obtain adequate images for stenosis assessment, which showed that the models presented homogeneous injury after scraping and developed a mature scar stricture at 28 days postoperatively with a mean stenosis degree of 65.9%, and 71.4% (10/14) above Myer–Cotton’s grade II. The pathological findings were consistent with the clinicopathological process of human. No stenosis was found in mock group. Conclusion: The modified model is simpler, minimally invasive and reliable, while the household endoscope is competent for model’s follow-up, providing easily accessible and useful tools for facilitating more extensive studies of benign tracheal stenosis.